Banks' option to lend, interest rate sensitivity, and credit availability - Iftekhar Hasan; Sarkar Sudipto (Bank of Finland, 2002)
Interest rate risk is a major concern for banks because of the nominal nature of their assets and the asset-liability maturity mismatch.This paper proposes a new way to derive a bank's interest rate sensitivity, by examining separately the effects of interest rate changes on existing loans (loans-in-place) and potential loans (loans-in-process).A potential loan is shown to be equivalent to an American option to lend, and is valued using option theory.An increase in interest rates usually has a negative effect on existing loans.However, if both deposit and lending rates rise by the same amount, the value of a potential loan generally increases. Hence a bank's lending slack (ratio of loans-in-process to loans-in-place) will determine its overall interest rate risk. Empirical evidence indicates that low-slack banks indeed have significantly more interest rate risk than high-slack banks.The model also makes predictions regarding the effect of deposit and lending rate parameters on bank credit availability.Empirical tests with quarterly data are generally supportive of these predictions.
URN:NBN:fi:bof-20140807159
Keywords: 330; interest rate risk; option to lend; bank's lending capacity; maturity intermediation